STUDENTSâ PERCEPTIONS ON THE IMPLEMENTATION OF PROJECT BASED LEARNING IN ENTERPRENEURSHIP CLASS - Kayyis, Rahmatika (STKIP Muhammadiyah Pringsewu, 2016)
Project based learning is teaching method that offer learner autonomy and freedom to beenggaged with their le arning activity. From that also the learner can learn theirlanguage (L2) by doing their project conciously or unconciously.Project-basedlearning was suceed to be implemented in the class of enterpreneurship class. In thisproject, 62 students were divided into 31 pairs and asked to do the project onbuilding their own bussiness. The bussiness should be based on language skills. Thedata were collected mainly from studentsâ essays, writen at the end of semester, onthe advantages and disadvantages of using project-based learning in classroom. Thedata were then analyzed both quantitatively and qualitatively. The quantitativeanalysis was first used for assessing the responses obtained from the essays; andsecondly, the qualitative analysis provided the evaluation and interpretation of thefigures. The results showed that most students appreciated the use of PBL in theclassroom because the method made them to be more independent in learning of howto teach using English and use their talent in creating bussiness.Beside this alsoevoke the students willingness to do their project in creating bussiness, Englishcourses.Keywords: project, teaching and learning method, enterpreneursihp, bussiness